2023
DOI: 10.3389/fsoc.2023.1260407
|View full text |Cite
|
Sign up to set email alerts
|

Gender trait preferences among smallholder cowpea farmers in northern Ghana: lessons from a case study

Alhassan Nuhu Jinbaani,
Emmanuel Yaw Owusu,
Abdul-Razak Mohammed
et al.

Abstract: IntroductionThis case study reports on how a gender responsive breeding program contributes to meeting the trait preference of men and women for improved cowpea varieties in northern Ghana.MethodsFifty-eight early-maturing, medium-maturing and dual-purpose cowpea lines were planted at the CSIR-SARI research fields and women and men farmers invited for participatory plant breeding (PPB) in 2016. Selected lines from the PPB were further evaluated in 2017 using participatory varietal selection (PVS) in 5 district… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…There are efforts in plant breeding to collect gender-sensitive data and understand how and when gender differentiated research on plant traits is necessary. Commonly, trait preference studies use direct ranking (Jinbaani et al, 2023) or choice experiments (Waldman et al, 2014) but these methods give little attention to the social structures and roles and responsibilities within households that shape those preferences (Teeken et al, 2021). Furthermore, a recent review of gender and plant breeding research showed that even when genderdifferentiated data were collected for assessing farmers' preferences for plant traits, gender differentiated analyses were rare (Weltzien et al, 2019a).…”
Section: Gender In Plant Breedingmentioning
confidence: 99%
“…There are efforts in plant breeding to collect gender-sensitive data and understand how and when gender differentiated research on plant traits is necessary. Commonly, trait preference studies use direct ranking (Jinbaani et al, 2023) or choice experiments (Waldman et al, 2014) but these methods give little attention to the social structures and roles and responsibilities within households that shape those preferences (Teeken et al, 2021). Furthermore, a recent review of gender and plant breeding research showed that even when genderdifferentiated data were collected for assessing farmers' preferences for plant traits, gender differentiated analyses were rare (Weltzien et al, 2019a).…”
Section: Gender In Plant Breedingmentioning
confidence: 99%